Reperfusion strategy and in-hospital outcomes for ST elevation myocardial infarction in secondary and tertiary hospitals in predominantly rural central China: a multicentre, prospective and observational study - Shan Wang; Zheng Liu; Ling Zhang; Peng Liu; Wei Wei; Dongsheng Wang; Yi Yang; Chuanyu Gao; Na Sun; Haiyan Sun; Haitao Wang; Lianjie Li; et al. (BMJ Open, 2021)
Objectives To assess differences in reperfusion treatment and outcomes between secondary and tertiary hospitals in predominantly rural central China.Design Multicentre, prospective and observational study.Setting Sixty-six (50 secondary and 16 tertiary) hospitals in Henan province, central China.Participants Patients with ST elevation myocardial infarction (STEMI) within 30 days of symptom onset during 2016–2018.Primary outcome measures In-hospital mortality, and in-hospital death or treatment withdrawal.Results Among 5063 patients of STEMI, 2553 were treated at secondary hospitals. Reperfusion (82.0% vs 73.0%, p<0.001) including fibrinolytic therapy (70.3% vs 4.4%, p<0.001) were more preformed, whereas primary percutaneous coronary intervention (11.7% vs 68.6%, p<0.001) were less frequent at secondary hospitals. In secondary hospitals, 53% received fibrinolytic therapy 3 hours after onset, and 5.8% underwent coronary angiography 2–24 hours after fibrinolysis. Secondary hospitals had a shorter onset-to-first-medical-contact time (176 min vs 270 min, p<0.001). Adjusted in-hospital mortality (adjusted OR 1.23, 95% CI 0.89 to 1.70, p=0.210) and in-hospital death or treatment withdrawal (adjusted OR 1.18, 95% CI 0.82 to 1.70, p=0.361) were similar between secondary and tertiary hospitals.Conclusions With fibrinolytic therapy as the main reperfusion strategy, the reperfusion rate was higher in secondary hospitals, whereas in-hospital outcomes were similar compared with tertiary hospitals. Public awareness, capacity of primary and secondary care institutes to treat STEMI, and establishment of deeper cooperation among different-level healthcare institutes need to further improve.Trial registration number NCT02641262.